2006
DOI: 10.1007/s10147-006-0568-3
|View full text |Cite
|
Sign up to set email alerts
|

Current status and perspective of angiogenesis and antivascular therapeutic strategy: non-small cell lung cancer

Abstract: Lung cancer is the leading cause of cancer death worldwide, and most patients die of metastatic disease. Angiogenesis, namely, neovascularization from preexisting vasculature, is necessary for tumor growth in both primary and distant organs to supply oxygen and nutrition. Angiogenesis consists of sprouting and nonsprouting (the enlargement, splitting, and fusion of preexisting vessels) processes, and both can occur concurrently. The growth of non-small cell lung cancer (NSCLC), which accounts for more than 80%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…In this tumor model, potentially due to the ablation of the natural killer cells, large numbers of hepatic and osteolytic metastatic lesions were observed. This confirms the prior study of bone metastasis by these tumors (21), supporting this as an exciting model for organ-specific metastasis studies.…”
supporting
confidence: 86%
“…In this tumor model, potentially due to the ablation of the natural killer cells, large numbers of hepatic and osteolytic metastatic lesions were observed. This confirms the prior study of bone metastasis by these tumors (21), supporting this as an exciting model for organ-specific metastasis studies.…”
supporting
confidence: 86%
“…Angiogenesis is regulated by the balance of proangiogenic molecules, such as vascular endothelial growth factor, fibroblast growth factor-2, interleukin-8, and antiangiogenic molecules, such as thrombospondin-1, angiostatin, and endostatin (41). Whereas the roles of FST and activin in angiogenesis still remain controversial (42), several reports showed that activin induces the expression of vascular endothelial growth factor and that it controls tubulogenesis of endothelial cells (39,43,44).…”
Section: Discussionmentioning
confidence: 99%
“…8,20 A correlation between the degree of angiogenesis and systemic metastasis has been reported in a variety of malignant tumors, including lung cancer. 22,34 Variable results have been reported concerning the prognostic implications of serum VEGF levels in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…4 -6 Angiogenesis is controlled by the interplay of numerous positive and negative factors, 7 and proangiogenic factors include many growth factors, proteases, and cytokines. 8 Of these, vascular endothelial growth factor (VEGF) is the most extensively studied and is significantly related to tumor progression, metastasis, and prognosis. 9 -11 Angiopoietins play an important role in angiogenesis in concert with VEGF.…”
mentioning
confidence: 99%